In search of the meaning-making student : Notes on the lack of third-order concepts in the Finnish history curriculum Att söka efter den meningsskapande studenten : Iakttagelser om bristen av third-order begrepp i de finländska läroplanerna för historia - Löfström Jan (Institutt for lærerutdanning og skoleforskning Universitetet i Oslo, 2025)
In this article, the current Finnish history curricula for basic education and upper secondary school are analysed from the perspective of what space they give to the students’ personal meaning-making activity in teaching and learning of history. This is a pertinent question, considering that history is often mentioned as a subject where students process the issues of identity, worldview and values. The research question is: Where and how is the students’ processing of their personal relationship with history addressed in the curriculum? The material consists of the history section in the national core curricula for basic education (2014) and upper secondary school (2019) and in the criteria for final assessment in basic education (2020). The method is qualitative theory-driven content analysis. The result is that the students’ personal meaning-making activity is referred to in the general task and the learning objectives of history teaching and learning and in the assessment criteria of history learning but not in the content of history teaching. As the student as a meaning-making agent does not appear where the content of teaching is outlined in concrete terms, there may be only little inspiration for the history teachers to discuss history’s personal meaning in the classroom. This can explain why Finnish students have had difficulty to understand, for example, why questions of historical wrongs can be experienced as transgenerationally relevant and alive.
I denna artikel analyseras vilket utrymme ges åt studenters personliga meningsgivande aktivitet i historieundervisning i de finländska läroplanerna för historia som nu är i kraft. Temat är relevant med tanke på att historia ofta nämns som ett skolämne där studenter processerar frågorna kring identitet, livssyn och värden. Forskningsfrågan är var och hur studenternas processerande av sitt personliga förhållande med historia hänvisas till i läroplanerna. Materialet utgörs av kapitlen på historia i läroplansgrunderna för den grundläggande utbildningen (2014) och för gymnasiet (2019) och bedömningskriterierna för slutbedömningen i den grundläggande utbildningen (2020). Metod är kvalitativ teoristyrd innehållsanalys. Resultatet är att studenters personliga meningsgivande aktivitet bara hänvisas till i beskrivningen av historieundervisningens allmänna uppdrag och inlärningsmål och i bedömningskriterierna men inte i beskrivningen av historieundervisningens innehåll. Studenten som en meningsgivande aktör syns inte där undervisningens innehåll mest konkret utstakas; det betyder att där finns lite inspiration för historielärare att diskutera historiens personliga mening i klassrummet. Detta kan förklara varför finländska studenter har haft svårigheter att begripa, till exempel, varför frågor om historiska orättvisor kan upplevas som transgenerationellt relevanta och levande.